DESCRIPTION OF SELF-DISCLOSURE ON SOCIAL MEDIA: A USER STUDY OF INSTAGRAM STORY'S CLOSE FRIEND FEATURE - OFTHA DEYANDA; Rizal Kurniawan (In Trend : International Journal of Trends in Global Psychological Science and Education, 2025)
This study aims to describe self-disclosure in users of the Close Friend Instagram Story feature and determine the psychological impact of using the feature. The Close Friend feature allows users to share personal stories and information exclusively with selected friends, thus providing a safer and more private space than the public Instagram Story. The research method used is a descriptive qualitative approach with thematic analysis. Data was obtained through an open-ended questionnaire distributed online to 314 participants who are active users of the Close Friend feature. The results showed that the main reasons users choose the Close Friend feature are to maintain privacy, increase their sense of comfort, and reduce social pressure. In addition, self-disclosure on the feature is driven by emotional closeness and a sense of security towards selectively chosen close friends. The perceived psychological impact includes feelings of relief, happiness, and increased self-confidence. However, some users also felt anxiety due to the potential spread of personal information. The conclusion of this study confirms that the Close Friend Instagram Story feature is an effective medium for more intimate and private self-disclosure, although it still holds risks to user privacy.